Persepsi Masyarakat Desa Parado Rato Terhadap Penggunaan Akad Musyarakah dalam Pertanian - Putri Miftahul Jannah; Ihwan P. Syamsudin; Umar Sagaf (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the perception of the Parado Rato Village Community towards the use of the Musyarakah Agreement in the Agricultural sector. The Musyarakah Agreement is a form of cooperation in Islamic Economics that allows two or more parties to participate in capital and share profits based on an agreement. Although this agreement has great potential to be applied in the Agricultural sector, the application of this concept in rural communities has not been widely studied, especially in the context of trust, understanding, and acceptance. The research method used is a Qualitative Approach with Data Collection Techniques through in-depth interviews, Observation, and Documentation. Respondents consisted of Farmers, Religious Figures, and Village Leaders in Parado Rato who have experience in Agricultural activities. The results of the study show that Community Perception of the Musyarakah Agreement is influenced by factors of Education, understanding of Islamic Economics, and experience in business work. Most respondents showed a Positive attitude towards the use of this Agreement because it is in accordance with the principles of justice and mutual cooperation. However, there are obstacles in the form of limited understanding of the Musyarakah Agreement mechanism which often hinders its optimal implementation. Based on the analysis of the data obtained, the conclusion is that although the Parado Rato Village Community has a positive perception of the use of the Musyarakah Agreement, further socialization and education are needed to improve understanding and application of this Agreement in the Agricultural sector.